2021
DOI: 10.3389/fped.2020.598724
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Monocyte and Neutrophil Functional Phenotype in Infants With Neonatal Encephalopathy Requiring Therapeutic Hypothermia

Abstract: Neonatal encephalopathy (NE) is a significant cause of morbidity and mortality. Persistent inflammation and activation of leukocytes mediate brain injury in NE. The standard of care for NE, therapeutic hypothermia (TH), does not improve outcomes in nearly half of moderate to severe cases, resulting in the need for new adjuvant therapies, and immunomodulation holds promise. Our objective was to explore systemic leukocyte phenotype in infants with NE and healthy controls in response to lipopolysaccharide (LPS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Munoz et al demonstrated a reduced LPSinduced production of cytokines of IL-1α, IL-1β, IL-6, and TNF-α production in adult patients with sepsis, which was exacerbated in non-survivors (29). We demonstrated a hypo-responsiveness to LPS in NE infants with lower leucocyte activation markers of CD11b and NOX2 as compared with healthy term neonatal controls (17).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Munoz et al demonstrated a reduced LPSinduced production of cytokines of IL-1α, IL-1β, IL-6, and TNF-α production in adult patients with sepsis, which was exacerbated in non-survivors (29). We demonstrated a hypo-responsiveness to LPS in NE infants with lower leucocyte activation markers of CD11b and NOX2 as compared with healthy term neonatal controls (17).…”
Section: Discussionsupporting
confidence: 49%
“…Inclusion criteria of infants with NE undergoing TH and healthy term control infants were enrolled in the study as per our previous publications (2,17). Neonates at risk of NE, as per Huang et al criteria (18), were recruited following informed consent and then subsequently divided into Sarnat stage for grade of NE (19).…”
Section: Study Populationmentioning
confidence: 99%
“…Studies in human patients with stroke have shown a high number of peripheral neutrophils being associated with the severity of injury [ 71 ], as well as in neonatal HI associated with poorer neurological outcomes [ 26 ]. It has been shown that TH has a minimal effect on peripheral immune cell counts in neonatal HI cases [ 72 ]; however, HI neonates undergoing TH have altered inflammatory responses compared to healthy infants [ 73 ]. It is commonly believed that an increase in neutrophil count after HIE is possibly associated with an infection and adverse outcome; however, evidence has shown no significant changes in the neutrophil count in asphyxiated newborns [ 27 ], even less during TH [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two possible peripheral sources of purine release during and following NE include muscle tissue following increased muscle activity and systemic inflammation. While muscle activity is an unlikely source, as neonates with and without NE present similar behaviors [e.g., neonatal seizures are often accompanied by only subtle changes in behavior, further complicating their diagnosis ( Murray et al, 2016 )], there is a substantial body of evidence demonstrating altered immune responses (e.g., neutrophil activation) post-NE possibly contributing to increased purine/adenosine concentrations ( Barletta et al, 2012 ; Karmakar et al, 2016 ; Wang and Chen, 2018 ; O’Dea et al, 2020 ; Kelly et al, 2021 ). Of note, similar to increased blood purines in infants with seizures, inflammation markers are also highly associated with seizures ( Zareen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%